Masjid Agung Tuban Tahun 1987-2020 - Nafita Nur Ameliaa; M. Ridwan Abu Bakar (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2021)
Abstract: This article aims to examine the historical side of the Great Mosque of Tuban with a focus on the scope of discussion on its function for social aspects in the period 1987-2020. The method used in this search is a historical research method with sociology as its approach. The scalpel uses Talcott Parsons' structural functional theory. This study presents the results of the conclusion that: 1) The mosque is a place to carry out all activities which contain elements of obedience. Meanwhile, the characteristics of mosques in Indonesia, especially in Java, are identical with the use of overlapping roofs, having a mihrab, located to the west of the main square, and having a square plan, such as the Great Mosque of Demak and the Menara Kudus Mosque; 2) Tuban Great Mosque was founded on July 29, 1894 by Raden Toemenggong Koesoemodikdo. Experiencing physical development occurred in the 1960s by adding the right and left porches, in 1987 there was a renovation with the aim of beautifying the shape of the building, in 2004 the total renovation was the addition of floors, left and right wings, six towers, five domes and a fountain . And in 2016 there was an improvement with the addition of 4 umbrellas in the courtyard of the mosque; 3) The Great Mosque of Tuban has broad functions, namely in the religious sector, social sector, and as a tourist attraction. Keywords: Great Mosque of Tuban, history, development, social-community functions